Introducing Aeromab Project (Aerospace Technologies applied to Biodiversity Conservation) - Mulero-Pázmány, Margarita Cristina; Negro, Juan-José; Ferrer, Miguel; Puentes, Luna; De Lucas, Manuela (My University, 2008)
The AEROMAB Project (2008-2012) aimed to apply aerospace technologies, specifically Unmanned Aerial Systems (UAS), to biodiversity conservation. Conducted by the Doñana Biological Station (CSIC), the project focused on using UAS for wildlife monitoring, vegetation characterization, and assessing the impact of powerlines and windfarms on bird populations. Key objectives included developing methods to evaluate bird risks from powerlines, detecting bird casualties, and using UAS for wildlife censuses and bird migration monitoring. The project tested various UAV systems, including those equipped with digital and thermal cameras for wildlife detection and monitoring.
Keywords: Biodiversidad - Gestión - Innovaciones tecnológicas; Drones; Wildlife